In situ ruminal degradability of silage of mango wastes (Mangifera indica L.) and maize stubbles - Guzmán, O.; Lemus-Flores, C.; Bugarín, J.; Bonilla, J.; González-Vizcarra, V.; Ly, J. (Cuban Journal of Agricultural Science, 2019)
This research was carried out in order to evaluate the ruminal degradability of different silage based on agroindustrial and mango wastes (Mangifera indica c.v. Tommy Atkins) with the addition of with 2 levels of maize stubble, molasses and agricultural urea. With a simple classification design to determine in situ ruminal degradability of DM in six silage alternatives, the nylon bag technique was used in four rumen fistulated sheep. Degradation times of DM were 0, 4, 8, 16, 34, 48, 72 and 96 hours. There was significant effect (P <0.05) of treatment between 0 and 48 h for DM degradation, with higher values in treatments with higher fruit content (85%). Apparently, treatments showed a degradation percentage similar to 72 and 96 h of incubation, with mean values of 73.1 and 75.1 %, respectively. Significant differences (P <0.05) were observed among silage types for immediately (a) and potentially degradable fraction (b), but not (P> 0.05) for the degradation kinetic constant (c) nor for potential degradation (a + b). Effective degradation was significant (P <0.05) in silages with a higher content of mango wastes compared to the other four types of materials. It is concluded that treatments with the highest content of whole fruit or industrial waste, demonstrated the best degradation, maybe due to its high content of fermentable material. It is suggested to srudy performance tests in ruminants fed with silage from mango wastes, as well as to carry out in vivo digestion studies. Key words: chemical composition, mango waste, silage, ruminal degradation